Relasi Ergonomi Ruang Laboratorium Perkantoran dengan Kenyamanan, Kelelahan, dan Konsentrasi Mahasiswa - Dima Salsabila Gunawan; Puput Oktaviani; Harmon Chaniago (JURNAL ADMINISTRASI KANTOR, 2025)
This study aimed to analyze the relationship between office laboratory ergonomics and students’ comfort, fatigue, and concentration in a vocational learning environment. The study was based on the importance of ergonomic space design in supporting physical well-being and cognitive performance during computer-based and documentation activities. A quantitative approach with a correlational design was employed, involving fifty second-year students as respondents. Data were collected using a Likert-scale questionnaire and analyzed through validity testing, reliability testing, descriptive statistics, correlation, and simple linear regression. The findings showed that the ergonomic conditions of the laboratory were rated as good and had a positive relationship with comfort and concentration, as well as a negative relationship with fatigue. Regression results indicated that ergonomics significantly influenced comfort by fifty-two percent, fatigue by thirty-four percent, and concentration by forty-eight percent. These results demonstrated that ergonomic design played an essential role in enhancing learning effectiveness and reducing physical and mental strain during laboratory activities.